2017
DOI: 10.1080/00016357.2017.1347822
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of drugs prescribed for dental outpatients in Nigeria: findings and implications

Abstract: Polypharmacy, brand name prescriptions, and the frequent prescription of antimicrobials were common practices at the dental clinic of this teaching hospital in Nigeria. We suggest a review of the current standard treatment guidelines in Nigeria to guide dentists on current knowledge- and evidence-based treatment of common oral diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
2
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 54 publications
1
17
2
1
Order By: Relevance
“…The most common oral infections are pulpitis and periapical periodontitis, for which antibiotics are not required . However, studies have shown that antibiotics are often prescribed for these conditions . The awareness of dentists regarding the rational use of antibiotics and their antibiotic prescribing behaviors are important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common oral infections are pulpitis and periapical periodontitis, for which antibiotics are not required . However, studies have shown that antibiotics are often prescribed for these conditions . The awareness of dentists regarding the rational use of antibiotics and their antibiotic prescribing behaviors are important.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 However, studies have shown that antibiotics are often prescribed for these conditions. 5,6 The awareness of dentists regarding the rational use of antibiotics and their antibiotic prescribing behaviors are important. However, studies have found arbitrary and unnecessary prescribing practices by dentists due to many factors, mainly lack of knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, periodontal and gum diseases were the commonest diagnoses for patients attended a dental clinic in Nigeria (68.1%). 11 This difference in the pattern of diseases presenting to the dental clinic is reflected in the percentage and type of specific drugs prescribed to these patients in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although drug selection is performed appropriately with the other criteria, the disregard of cost means 'irrational drug practice' and this is particularly observed in the selection of antibiotics among dentists [13,24]. The selection of more expensive drugs rather than using cheaper generic drugs significantly increases treatment costs and causes an additional burden to the health economy and for the country, which is unfortunately observed more frequently in developing countries [6,25].…”
Section: Discussionmentioning
confidence: 99%
“…It was identified in many studies on prescribing medicine that the appropriate prescribing of antibiotics was a significant problem in dentistry facilities. It was stated that the most important cause of this problem generally stemmed from not complying with the available treatment guidelines [6]. There was a tendency of prescribing analgesics in addition to antibiotics among dentists because infection mainly caused pain [7][8][9].…”
Section: Introductionmentioning
confidence: 99%